2018
DOI: 10.3389/fphys.2018.00612
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanism Underlying Pro-apoptotic Role of Hemocytes Specific Transcriptional Factor Lhx9 in Crassostrea hongkongensis

Abstract: Hemocytes are the central organ of immune defense against pathogens by means of inflammation, phagocytosis, and encapsulation in mollusks. The well-functioning of the host immune system relies on the hemocytes’ task exertion and frequent renewal, but the underlying renewal mechanism remains elusive at the gene level. Here, we identified one transcription factor, LIM homeobox 9, in Crassostrea hongkongensis (ChLhx9) that could be involved in hemocyte apoptosis or renewal. ChLhx9 contains a homeodomain and two L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Many studies have demonstrated that long-term environmental changes can lead to dynamics in transcriptome and epigenetic marks. This may result in fine-scale adaptive divergence among populations and help organisms acclimate to the environment ( Kenkel and Matz, 2016 ; Zhou et al, 2018 ). Our previous study showed that CNS population abalones had greater thermal tolerance abilities than those from the CNN population ( Chen N. et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that long-term environmental changes can lead to dynamics in transcriptome and epigenetic marks. This may result in fine-scale adaptive divergence among populations and help organisms acclimate to the environment ( Kenkel and Matz, 2016 ; Zhou et al, 2018 ). Our previous study showed that CNS population abalones had greater thermal tolerance abilities than those from the CNN population ( Chen N. et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We designed gene-specific primers (Table 1 ) based on ORF to amplify gene fragments ~250 bp in length. Amplifications of actin and elongation factor 1α gene (EF1α) fragments were performed in order to confirm the steady-state level of expression of housekeeping genes, providing an internal reference for gene expression (Zhou et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Septin 11 isoform X1 was also strongly correlated with eigenvector 1. Septins have proapoptotic functions (Zhou et al, 2018), and in oysters, septins change abundance following pathogen exposure (Modak & Gomez‐Chiarri, 2020).…”
Section: Resultsmentioning
confidence: 99%